Meningkatkan Efektivitas Penerapan Langkah Keselamatan Sebagai Tindakan Preventif di Kapal AHTS Peteka 5402 - Egbert Edward Djajasasana; Wahyu Indarti; Joko Purnomo (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
Safety in the maritime sector, especially on Anchor Handling Tug Supply (AHTS) vessels, is a very crucial aspect in maintaining the sustainability of operations and preventing the potential risk of accidents at sea. One of the AHTS vessels that needs serious attention regarding safety aspects is the Peteka 5402 AHTS Ship. This study aims to understand and improve the effectiveness of the implementation of safety measures as a preventive measure on the ship. The research method used in this study is a qualitative method that produces descriptive data in the form of written words from oral interviews of crew members and observed behavior on the ship.